SPE Annual Technical Conference and Exhibition 2004
DOI: 10.2118/90096-ms
|View full text |Cite
|
Sign up to set email alerts
|

Analisis of Oil-Water Flow Tests in Horizontal, Hilly-Terrain, and Vertical Pipes

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractThe flow pattern, pressure drop and water holdup were measured for oil-water flow in horizontal, hilly-terrain (± 0.5° and ± 3°) and vertical pipelines at a temperature of about 35 ± 5 °C and a pressure of about 245 kPa using the large-scale multiphase flow-test facility of Japan Oil, Gas and Metals National Corporation (JOGMEC). Test lines of 4.19 inch (106.4 mm) ID and 120 m total length were utilized which included a 40 m horizontal or hilly-terrain and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…(Average pressure gradient measured for water at q : 0°, l w : 1 is 37 Pa/m) 3.3 Frictional pressure drop and the mixture velocity at θ = +5° and λ w = 0.9 6 shows, increment of frictional pressure drop with increment of mixture velocities. Lum et al [5], Abduvayt et al [8] and Kumara et al [7] also report the same trend. For higher watercut cases as λ w = 0.9, the flow is water dominant.…”
Section: Water Hold-upmentioning
confidence: 59%
“…(Average pressure gradient measured for water at q : 0°, l w : 1 is 37 Pa/m) 3.3 Frictional pressure drop and the mixture velocity at θ = +5° and λ w = 0.9 6 shows, increment of frictional pressure drop with increment of mixture velocities. Lum et al [5], Abduvayt et al [8] and Kumara et al [7] also report the same trend. For higher watercut cases as λ w = 0.9, the flow is water dominant.…”
Section: Water Hold-upmentioning
confidence: 59%
“…Several authors have reported the effect of pipe inclination angles on flow patterns [2,[43][44][45], pressure drop [44,46,47], liquid holdup [43,44,[46][47][48][49], drop velocity [48], drag-reducing polymers [50], and HTCs [41,51,52] in two-phase oil-water flows. Boostani et al carried out an experimental investigation and artificial neural network (ANN) model to resolve the HTC, and flow pattern for oil-water flows in inclined and horizontal pipes.…”
Section: Introductionmentioning
confidence: 99%